Cognitive therapy, working memory training, and the treatment of Methamphetamine Use Disorder - a functional MRI study - Dias, Angelo Ridge (Department of Psychiatry and Mental Health, 2021)
Background: In recent years, methamphetamine use disorder (MUD), which is associated with adverse outcomes and represents a significant public health burden, has become highly prevalent in Cape Town, South Africa. Protracted methamphetamine (MA) use has been linked with neural dysfunction and working memory deficits. Although current treatments have shown limited efficacy in addressing MUD, recent evidence indicates the potential of utilizing tailored brief cognitive therapy programs and working memory training to improve outcomes. The current study aims to investigate the potential impact of brief cognitive therapy and using working memory training as an adjunct in the treatment of MUD. Methods: Participants were recruited from an in-patient drug rehabilitation centre in Cape Town. The sample (n = 26) consists of male patients (between the ages of 18–50) diagnosed with MUD. MUD patients were randomly split into 2 groups that received 4 weeks of treatment, i.e. treatment as usual (cognitive therapy only (NT) (n= 12)) and cognitive therapy with working memory training (CT) (n = 14). Neuroimaging and psychological data were collected from participants pre- and post- intervention to assess the relative impact of said interventions. Results: Behavioural outcome measures and the n-back working memory task adapted for fMRI were measured and compared pre- and post- intervention. No significant differences were present between groups prior treatment on behavioural measures, demographic measures, and fMRI activity. The brief cognitive therapy appeared to reduce depression and impulsivity scores over the course of the intervention, with scores slightly lower in the CT group. An FDR corrected whole-brain repeated measures ANOVA on the main effect of group indicated significant activation in the left posterior cingulate, left anterior cingulate, and left lingual gyrus. Post hoc t-tests were then conducted to follow up the group main effect and significant differences under FDR correction were observed in the NT group (in contrast to the CT group) indicating significantly more activity in the left superior temporal gyrus, left insula, right posterior declive, and right lingual gyrus. Significant differences were also observed under FDR correction on a posthoc test on the CT group (in contrast to the NT group) indicating significantly less activity in the left lingual gyrus, left posterior declive, and right cuneus. 5 Conclusions: The findings tentatively suggest that the working memory training adjunct may have slightly enhanced working memory maintenance brain function relative to the treatment as usual group post-intervention. The evidence also suggests that there may have been inefficient neural functioning in the treatment as usual group during the working memory task compared to the group receiving the working memory training adjunct. The results demonstrated that brief cognitive therapy treatment did somewhat reduce depressive symptoms and impulsivity in this study, with indications of subtle treatment gains in the cognitive training group. Overall, the current study (despite numerous limitations) provides preliminary and tentative evidence of the possible benefits of brief term cognitive therapy and the potential promise of using working memory training as a treatment adjunct.